Państwo administracyjne - Supernat, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The term ‘administrative state’ is rather unknown in Poland and therefore not used both by academia and public officials. The text aims to ascribe to this term specific model meaning, which should allow us to place the term ‘administrative state’ in the administrative language and make administrative state a distinct field of research.
Keywords: state; administration; administrative law